Co (9) S (8) nanoparticle-supported nitrogen-doped carbon as a robust catalyst for oxygen reduction reaction in both acidic and alkaline conditions - Illathvalappil, Rajith; Kurungot, Sreekumar (ChemElectroChem, 2020)
The present work illustrates the synthesis of an efficient and durable catalyst for electrochemical oxygen reduction reaction (ORR) which is active both in the alkaline and acidic conditions by dispersing few-layer graphitic carbon coated Co(9)S(8)nanoparticles on the nitrogen-doped carbon (NVC-G) support (Co9S8/NVC-G). The size of the Co(9)S(8)nanoparticles is nearly 7-8 nm and the particles are found to be dispersed homogeneously on the NVC-G support. The few-layer graphitic carbon formed on the surface of Co(9)S(8)nanoparticles is assisting to accomplish their small size and it also prevents agglomeration of the nanoparticles. The ORR activity of the obtained material was analyzed in both 0.1 M KOH and 0.5 M H(2)SO(4)solutions. Co9S8/NVC-G displays nearly 70 mV overpotential compared to thestate-of-the-artPt/C in 0.1 M KOH solution. The half-wave potential (E-1/2) difference of the present system is nearly 75 mV with the commercial Pt/C. Co9S8/NVC-G displays promising ORR activity in the acidic conditions as well with nearly 140 mV overpotential compared to its Pt/C counterpart. The system shows about 170 mV lowerE(1/2)value with Pt/C. The system shows good stability both in acidic and basic conditions compared to the Pt/C system. Finally, testing of a single cell of a polymer electrolyte membrane fuel cell (PEMFC) was performed by employing Co9S8/NVC-G as the cathode catalyst and Nafion-212 as the proton exchange membrane. The system displays a maximum power density of 245 mW cm(-2)in H-2-O(2)and 115 mW cm(-2)in H-2-air feeding conditions.
Keywords: cobalt sulfide; fuel cells; Nanoparticles; nitrogen-doped carbon; oxygen reduction reaction